(untitled) (Research, Society and Development, 2020)
The foreign body reaction is an immune response that consists of a persistent inflammatory state in which a device, prosthesis, or biomaterial is rejected by the body, which induces its phagocytosis or unsuccessful degradation. After this frustrated elimination process, it causes the macrophages to fuse to form giant foreign body cells, and after the accumulation of collagen secreted by fibroblasts, the formation of a fibrous capsule occurs that isolates the biomaterial from the tissue medium. The treatment of this reaction consists of the surgical removal of the lesion with the subsequent regeneration of the defect, constituting the grafts and bone substitutes as the best therapeutic option and highlighting among these both autografts and allografts. In this review of the literature, the clinical case of a foreign body reaction in the maxilla is presented with its clinical and radiographic characteristics, treatment and postoperative clinical control.